Antioxidant and anticancer peptides from the protein hydrolysate of blood clam (Tegillarca granosa) muscle. (May 2015) - Chi, Chang-Feng; Hu, Fa-Yuan; Wang, Bin; Li, Tao; Ding, Guo-Fang
Highlights: High antioxidant hydrolysate from blood clam muscle (BCPH) was prepared. Two peptides with amino acid sequences of WPP and QP were isolated from BCPH. WPP showed high radical scavenging and lipid peroxidation inhibition activities. WPP showed strong anticancer activities on PC-3, DU-145, H-1299 and HeLa cell lines. Graphical Abstract: Abstract: In this study, two peptides isolated from the protein hydrolysate of blood clam ( Tegillarca granosa ) muscle were identified as Trp-Pro-Pro (BCP-A) and Gln-Pro (BCP-B), with molecular weights of 398.44 Da and 243.23 Da, respectively. Trp-Pro-Pro significantly inhibited lipid peroxidation and showed the highest radical scavenging activity among the hydrolysate, the hydrolysate fractions and the purified peptides with EC50 of 1.388, 0.406, 0.536 and 2.75 mg/ml against DPPH, HO, O2 -, and ABTS +, respectively. Furthermore, Trp-Pro-Pro showed strong cytotoxicity toward PC-3, DU-145, H-1299 and HeLa cell lines in a dose-dependent manner and significantly changed the morphologies of the PC-3 cells. The percentage of early stage apoptotic PC-3 cells increased from 11.22 to 22.78% when they were treated with Trp-Pro-Pro concentrations of 5 and 15 mg/ml, respectively, for 24 h. The finding indicated that Trp-Pro-Pro could be used to eliminate the excessive ROS produced under oxidative stress conditions and prevent cancers caused by a large number of free radicals. Furthermore, Trp-Pro-Pro could also be used for cancer therapy by scavenging free radicals and the induction of apoptosis of cancer cells. Therefore, Trp-Pro-Pro might serve as a natural antioxidant and anticancer agent for the nutraceutical and pharmaceutical industries.